Pituitary disorders in pregnancy - Darran Mc Donald; Maria Tomkins; Michael W. O’Reilly; Mark Sherlock (Clinical Medicine)
The management of pituitary disorders in pregnancy presents a unique challenge for maternal medicine specialists and endocrinologists. Advances in assisted reproductive technologies (ART) mean that women with hypopituitarism are increasingly able to conceive. The pituitary undergoes significant physiological changes during pregnancy. Pituitary hormone replacement regimens must therefore be adjusted throughout pregnancy in an attempt to mimic these changes. Close clinical and biochemical follow-up and collaboration across specialties is essential to ensure optimal maternal and fetal outcomes. Although many women with hypopituitarism will have a normal pregnancy, rates of miscarriage, labour induction and caesarean sections are higher than the general population. Most women with hypopituitarism are diagnosed prior to pregnancy; however, some pituitary disorders including lymphocytic hypophysitis, Sheehan’s syndrome and pituitary apoplexy have a predilection to arise during pregnancy or the postpartum period. Prompt recognition of these disorders is essential to prevent potentially fatal complications and optimise maternal and fetal wellbeing.